The Effectiveness of Online and Conventional Learning Models on the Learning Achievement of Semester IV Students of STAB Kertarajasa - Nurhayati; Nurhayati (Perspektif Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effectiveness of the learning model on student achievement in the fourth semester of STAB Kertarajasa in the Covid-19 pandemic period for the 2020/2021 academic year. The design used for the research is in the from of an experiment with a quantitative approach. The instrument used in this study was a questionnaire distributed 23 fourth semester student of STAB Kertarajasa. The data that has been obtained from the questionnaire distribution is then analyzed using a likert scale and the GPA value of online and conventional learning model is analyzed by t-test.                        The result of this research is that the online learning model is classified as easy with 59% achievement percentage. for conventional learning models are also classified as easy with a percentage of 69% achievement. based on the t-test the GPA values ​​of online and conventional learning models are in the real area. Keywords: online learning, conventional learning, learning achievement